Militarization and war - Schofield, Julian (Initiatives in strategic studies--issues and policies, 2007)
There is a consensus among proponents of militarism theory that militaries seek wars to enhance their institutional influence, promoting expansionist policies because it is in line with their training. However, most military-run states, and those regimes influenced by their militaries, termed militarized regimes, spend much of their time at peace. This book questions the underlying logic of the militarist expansion and seeks to propose a more tragic argument based on the distorting impact of military indoctrination and command practices on civil government institutions. The theory is applied to seven case studies of the periods leading up to the 1965 and 1971 Indo-Pakistan Wars, the 1956, 1967, and 1973 Arab-Israeli Wars, the 1969-75 Iran-Iraq border conflict, and the 1979 Iraqi invasion of Iran.